Hesperidin protects rats’ liver and kidney from oxidative damage and physiological disruption induced by nickel oxide nanoparticles - Abd-Eltawab Tammam, Ahmed; A. Khalaf, Abdel Azeim; R. Zaki, Amr; Mansour Khalifa, Mohamed; A. Ibrahim, Marwa; M. Mekkawy, Aya; E. Abdelrahman, Rehab; Farghali, Ahmed; A. Noshy, Peter (Frontiers in Physiology, 2022)
Background: Nickel oxide nanoparticles (NiO-NPs) have recently been utilized in various advanced industrial fields like lithium-ion micro batteries, nanofibers, electrochromic devices, and several biomedical applications. NiO-NPs are classified as extremely toxic substances as they can cause long-term harm to the environment and aquatic life. Moreover, frequent and prolonged exposure can affect human and animal health, causing skin allergies and major toxic consequences, such as hepatorenal toxicity. Hesperidin (HSP) has been proven to possess anti-inflammatory, antioxidant, and free radical scavenging activities. Objective: This study aimed to investigate the underlying protective mechanisms and effects of HSP against NiO-NPs-induced hepatorenal toxicities in rats. Materials and Methods: Forty male Wistar rats were randomly divided into four groups (n=10 in each). The first group served as a Control group. For 8 weeks, the second group was administered NiO-NPs (100 mg/kg/day), and the third group was given HSP (100 mg/kg/day) via oral gavage for both groups. The fourth group received NiO-NPs and HSP concurrently in the same oral daily doses and duration as the second and third groups. Results: NiO-NPs administration revealed a significant increase in plasma biomarkers of nephrotoxicity (urea, creatinine) and hepatotoxicity (ALT, AST) in NiO-NPs group compared to Control group (p < 0.05). In addition, NiO-NPs administration resulted in a substantial increase in malondialdehyde levels with a significant drop in catalase activity and GSH content in Group II. Also, a significant decreased expression of Nrf-2 and Bcl-2 mRNA levels and upregulation of TNF-α, NF-kβ and BAX in the liver and kidney of NiO-NPs group were also detected. Histologically, the liver and kidney of rats of NiO-NPs group showed significant histopathological disturbances, with a substantial increase in the proliferating cell nuclear antigen (PCNA) positive hepatocytes and renal tubular cells in the NiO-NPs group compared to Control and HSP groups (p < 0.05). In contrast, concomitant administration of HSP with NiO-NPs in group IV showed a significant biochemical, histopathological, and immunohistochemical improvement compared to NiO-NPs group. Conclusion: Co-administration of HSP with NiO-NPs significantly ameliorated most of the NiO-NPs-induced hepatorenal toxicities in male rats.